Ecumenism: Unity in Diversity - Kochappilly, Paulachan (Journal of Dharma, 2006)
Kuncheria Pathil, Ecumenism: Unity in Diversity, Bangalore: Dharmaram Publications, 2006, pages: ix + 215, ISBN: 81-86861-93-9.